Psychological and Neural Mechanisms of Subjective Time Dilation - van Wassenhove, Virginie; Wittmann, Marc; Craig, A.D. (Bud); Paulus, Martin P. (Frontiers in Neuroscience, 2011)
For a given physical duration, certain events can be experienced as subjectively longer in duration than others. Try this for yourself: take a quick glance at the second hand of a clock. Immediately, the tick will pause momentarily and appear to be longer than the subsequent ticks. Yet, they all last exactly one second. By and large, a deviant or an unexpected stimulus in a series of similar events (same duration, same features) can elicit a relative overestimation of subjective time (or "time dilation") but, as is shown here, this is not always the case. We conducted an event-related functional magnetic neuroimaging (fMRI) study on the time dilation effect. Participants were presented with a series of five visual discs, all static and of equal duration (standards) except for the fourth one, a looming or a receding target. The duration of the target was systematically varied and participants judged whether it was shorter or longer than all other standards in the sequence. Subjective time dilation was observed for the looming stimulus but not for the receding one, which was estimated to be of equal duration to the standards. The neural activation for targets (looming and receding) contrasted with the standards revealed an increased activation of the anterior insula and of the anterior cingulate cortex. Contrasting the looming with the receding targets (i.e. capturing the time dilation effect proper) revealed a specific activation of cortical midline structures. The implication of midline structures in the time dilation illusion is here interpreted in the context of self-referential processes.